PELATIHAN DESAIN PRODUK MENGGUNAKAN TEKNOLOGI ADDITIVE MANUFACTURING DI SMK NEGERI 1 TANJUNG RAYA - Rifelino Rifelino; Zainal Abadi; Irma Yulia Basri (LPPM Universitas Abdurrab, 2025)
The purpose of the community service is to improve teachers' skill in terms of mechanical drawing and realize it in the form of prototype objects utilized additive manufacturing technology at Vocational High Schools in Tanjung Raya-Agam Regency. The workshop material consists of 3D digital drawing designs using the AutoCad software, slicing parameter settings through the Cura software, furthermore the printing process on a 3D printing machine. Lecture technique was applied in terms of conveying teaching materials, discussions, demonstrations, and individual tasks. The tasks of digital drawing transformed into 3-dimensional objects through a printing process on machine. The workshop completed in 2-day duration with 15 participants of productive subject teachers of mechanical engineering departmen. producing several products in the form of 3-dimensional alphabets, table top organizers, and gear profiles. Some of products produces such as 3D alphabets, table top organizers, and gear profile. The results of the workshop revealed that the teachers' competencies had increased in designing 3D objects and creating prototype objects on 3D printing machine. This is proven by several prototype products that were produced. The enthusiasm of the participants increased considering that 3D printing machine able to generate digital mechanical drawing into prototype products. The competencies taught during workshop provides stimulus to participants to be creative in generate 3D products such as decoration, merchandise and even miniatures that are used as learning media. The product results achieved after this training activity are satisfactory with good geometry, dimensions and neatness of objects.